EFEKTIVITAS KINERJA DINAS PEMBERDAYAAN PEREMPUAN, PERLINDUNGAN ANAK DAN KELUARGA BERENCANA DALAM PENCEGAHAN STUNTING DI KABUPATEN SIMEULUE - Reci Muliani; Nodi Marefanda (AS-SIYASAH : Jurnal Ilmu Sosial Dan Ilmu Politik, 2023)
The aim of this study was to determine the effectiveness level of DP3AKB's performance in preventing stunting in Simeulue District. This research was carried out at the Office of Women's Empowerment, Child Protection and Family Planning in Simeulue District. This research is a descriptive qualitative research where the research is carried out directly aimed at the informants as research objects. Data collection techniques were carried out in a triangulation (combined) manner, data analysis was inductive in nature, and the results of qualitative research emphasized meaning rather than generalization. The results of the study show that aspects of the duties or functions of the DP3AKB institution in preventing stunting in Simeulue Regency have been carried out effectively and the implementers have been carried out properly. Based on research, the effectiveness of the implementation of the Acceleration of Stunting Reduction program is quite effective because there are already cadres such as Toddler Family Development and outreach to the community about the program so that parents understand how stunting is prevented